EFFECTS OF TEMPERATURE AND AERATION ON THE DISSOLVED OXYGEN (DO) VALUES IN FRESHWATER USING SIMPLE WATER BATH REACTOR: A BRIEF REPORT - Febiyanto, Febiyanto (Walisongo Journal of Chemistry, 2020)
This work investigated the effect of temperature and aeration treatments on the dissolved oxygen (DO) values in freshwater. The study was carried out using a simple water bath reactor in room temperature condition. Based on the results, freshwater sample without the aeration and temperature treatments (control) indicates a fluctuating profile on which the obtained values of DO were 4.21-4.98 mg/L at Taverage = 27.7 °C. However, the aeration treatment was slightly able to enhance the DO value up to 8.12 mg/L from the initial concentration of 3.88 mg/L at Taverage = 27.4 °C. Compared to the aeration treatment, the addition of temperature treatment has extremely increased the DO value up to 21 mg/L from 6.6 mg/L (T0 minutes = 27 °C)  for 20 minutes of DO observation (T20 minutes = 12.4 °C). Hence, this brief report suggests that the addition of temperature treatment gave a significant effect on the DO value in freshwater than the aeration treatment and control.